The Majorana Demonstrator: A Search for Neutrinoless Double-beta Decay of 76Ge. (April 2015) - Xu, W; Abgrall, N; Avignone, F T; Barabash, A S; Bertrand, F E; Brudanin, V; Busch, M; Buuck, M; Byram, D; Caldwell, A S; Chan, Y-D; Christofferson, C D; et al.
Abstract: Neutrinoless double-beta (0 νββ ) decay is a hypothesized process where in some even-even nuclei it might be possible for two neutrons to simultaneously decay into two protons and two electrons without emitting neutrinos. This is possible only if neutrinos are Majorana particles, i.e. fermions that are their own antiparticles. Neutrinos being Majorana particles would explicitly violate lepton number conservation, and might play a role in the matter-antimatter asymmetry in the universe. The observation of neutrinoless double-beta decay would also provide complementary information related to neutrino masses. The Majorana Collaboration is constructing the MAJORANA DEMONSTRATOR, with a total of 40-kg Germanium detectors, to search for the 0 νββ decay of 76 Ge and to demonstrate a background rate at or below 3 counts/(ROI·t·y) in the 4 keV region of interest (ROI) around the 2039 keV Q-value for 76 Ge 0 νββ decay. In this paper, we discuss the physics of neutrinoless double beta decay and then focus on the MAJORANA DEMONSTRATOR, including its design and approach to achieve ultra-low backgrounds and the status of the experiment.